Effective transition from standing to groundwork combat: an analysis of judo athletes with visual impairments - Detanico, D.; Gulias, V. d. O. S.; Gomes, N. A. B.; Kons, R. L. (Frontiers in Sports and Active Living, 2025)
Judo for athletes with visual impairments (VI judo) requires constant adaptation of technical and strategic skills. The transition from standing to groundwork combat (tachi-waza to ne-waza) is a key phase that impacts match outcomes. VI judo athletes are classified into two groups: J1 (total blindness) and J2 (partially sighted), each facing distinct challenges. This study examined the effective transitions (those that resulted in scoring actions) from standing to groundwork combat in high-level VI judo athletes considering J1 and J2 sport classes. In this observational study, a total of 195 videos was analyzed, involving 146 VI judo athletes who competed at the Paris 2024 Paralympic Games. Chi-square tests were used to verify the associations between effective actions and transition outcomes, with significance level set at p < 0.05. Main results showed that J1 athletes had a higher frequency of effective transitions compared to J2 athletes [X² = 4.81; p = 0.028 (medium effect)], with osae-komi-waza (immobilization techniques) being the most used technique across both groups [X² = 11.24; p = 0.004 (large effect)] and results in ippon [X² = 6.80; p = 0.008 (medium effect)]. No significant differences were found between J1 and J2 athletes regarding transition pace, uke (athlete who receives the technique) body position and match status (p > 0.05). The results suggest that J1 athletes experienced higher frequency of effective transitions from standing to groundwork combat compared to J2 athletes considering osae-komi-waza techniques which results in ippon more frequently for both groups. These findings provide preliminary evidence on the performance characteristics of VI judo athletes, particularly regarding effective transitions to groundwork techniques. They also supply technical-tactical information that can support athlete development across sport classes under the new classification system.